The effectiveness of rice husk ash as additive in palm oil-based compost in enhancing the nitrogen uptake by brassica oleracea var. alboglabra L. (Chinese Kale) plant - Nor Hanuni, Ramli; Nur Eliza, Badrul Hisham; Nor Fhairna, Baharulrazi (Universiti Putra Malaysia, 2023)
Rice husk ash (RHA), palm oil mill effluent (POME) sludge, and decanter cake can be utilized as compost to reduce environmental pollution. This research attempted to investigate the effect of RHA addition to palm oil-based compost in boosting the nitrogen (N) uptake and the growth of Brassica oleracea var. alboglabra L. (Chinese kale plant). Two categories of compost treatment were prepared in this study: Treatment 1 (control) and Treatment 2 [consisting of 10% (wt/wt) of RHA]. Both treatments were composted for 60 days until it was matured. The temperature and pH of the composts were recorded daily throughout the study. The treatments were analyzed for moisture, water-holding capacity, and nutrient content. The Chinese kale plant was grown in growing media and applied with Treatment 1 and Treatment 2 composts. The progress of plant growth was tracked every week. Based on the analysis, Treatment 2 exhibited a higher temperature and pH profile than Treatment 1. Meanwhile, the contents of N, P, and K were higher in Treatment 1 compost. However, Treatment 2 compost had higher silicon (Si) content, moisture content, and water-holding capacity. Based on the field test study carried out on the Chinese kale plant, the N uptake, and the growth of the plant, were found to be significantly higher when applied with Treatment 2 compost compared to Treatment 1 by 19% to 31% and 13% to 53%, respectively. It was proven that the addition of 10% RHA managed to provide an adequate amount of Si, moisture content, and water-holding capacity in Treatment 2 compost that can enhance the N uptake and improve the growth of the Chinese kale plant in this study.